Bioactive properties of Agaricus bisporus and Terfezia claveryi proteins hydrolyzed by gastrointestinal proteases. (May 2018) - Farzaneh, Parisa; Khanahamadi, Morteza; Ehsani, Mohammad Reza; Sharifan, Anousheh
Abstract: The proteins of Terfezia claveryi and Agaricus bisporus were hydrolyzed by gastrointestinal enzymes. The degree of hydrolysis, type of enzymes and mushrooms, and blanching as pretreatment influenced the bioactivity properties of produced peptides. Some produced peptides from both mushrooms had more antioxidative and antimicrobial activity than their respective initial proteins (P < .05). The most effective samples were non-blanched intact protein of A. bisporus with absorbance of 0.305 ± 0.005 for reducing power and non-blanched and blanched pepsin-trypsin-α-chymotrypsin hydrolysates with 73.68 ± 1.79% and 77.77 ± 1.79% for DPPH scavenging activity, respectively. However, non-blanched Trypsin-α-chymotrypsin and non-blanched trypsin hydrolysates of T. claveryi were more effective for inhibition of linoleic acid oxidation with 85.85 ± 0.82% and chelating activity with 21.36 ± 0.84%, respectively. Besides, inhibition of growth of Pseudomonas aeruginosa and Bacillus cereus, as the most sensitive microorganisms, were 26.64 ± 0.79% by blanched trypsin hydrolysate of A. bisporus and 27.44 ± 0.62% and 27.00 ± 0.62% by the blanched trypsin and α-chymotrypsin hydrolysates of T. claveryi, respectively. Highlights: Proteolysis of Terfezia claveryi and Agaricus bisporus proteins alters their health promoting properties. Gastrointestinal enzyme combinations influenced bioactivity of released peptides. Blanching affected antioxidant and antimicrobial properties of hydrolysates. The kinetic and degree of hydrolysis was investigated with OPA and SDS-PAGE.